Pendampingan Pelatihan Musik Bagi Pemuda-Pemudi Ebenhaezer Bawuaya Sebagai Upaya Peningkatan Kemandirian Jemaat Beribadah (International Forum of Researchers and Lecturers, 2023)
Based on research on guitar music training for youth in church (GKSI) one of the goals is to help increase the independence of congregations for worship. teaching youth to play the guitar is in the ministry at the GKSI EBENHAEZER BAWUAYA church. One of the methods that will be held by God's servants for youth is one of the approaches. the method of approach used by God's servants in training skills/proficiencies for young people learning to play music (guitar) and so that it produces good and correct music playing techniques. in guiding mentoring and also teaching playing music (guitar) both done individually and collectively for the music team with the aim of increasing self-confidence to worship so that activities to learn to play music (guitar) can be carried out patiently and happily. In the process of learning to play the guitar, it is carried out using the training and mentoring method. through this method is done either orally or also in theory and also in practice. In training activities, results are assessed. We can do it together with the music training team with the song leader in the last music (guitar) playing activity carried out by the trainer.